Floodplain Inundation and Salinization From a Recently Restored First‐Order Tidal Stream. Issue 7 (4th July 2020) - Yabusaki, Steven B.; Myers‐Pigg, Allison N.; Ward, Nicholas D.; Waichler, Scott R.; Sengupta, Aditi; Hou, Zhangshuan; Chen, Xingyuan; Fang, Yilin; Duan, Zhuoran; Serkowski, John A.; Indivero, Julia; Wiese Moore, Cora; et al.
Abstract: The systematic response of coastal ecosystems to inundation and salinity exposure is fundamental to their ecology and biogeochemical function. Here we observe and model freshwater‐seawater interactions in a first‐order stream—floodplain system where tidal access was recently restored. Subsurface flow and transport modeling were used to quantify and better understand the interplay of processes, properties, and conditions that control water level and salinity in the floodplain to the tidal stream. Water levels in the stream were highly correlated with tidal forcing, which resulted in episodic inundation of the floodplain at quasi‐monthly frequency. The tidal stream is the only source of salinity to the floodplain, yet shallow groundwater salinity was considerably higher than average stream salinity. The low‐permeability clay floodplain soils limit lateral groundwater flow and transport, resulting in floodplain groundwater and salinity dynamics driven almost exclusively by infiltration during inundation events. As inundation occurs during high tide, estuarine waters reach the floodplain with minor attenuation in salinity from the stream's freshwater discharge. Infiltration and salinity exposure are topography controlled and regulated by ponding depth and duration, seasonal ground saturation, and depth to water table. The model suggests that floodplain salinity is currently in an early stage of transition from pre‐restoration freshwater conditions and will not reach equilibrium for ~20 years. These findings have broad relevance for understanding how and over what time scales coastal ecosystems will respond to increasing seawater exposure from sea level rise, ocean‐originating storms, and changes in natural and man‐made barriers. Key Points: Freshwater‐seawater interactions in a recently restored tidal stream‐floodplain system were evaluated with mechanistic modeling Salinity infiltration and water table dynamics in the floodplain were largely driven by quasi‐monthly tidal inundation events Floodplain salinity is currently at an early stage of transition from the pre‐restoration freshwater conditions